Prophetic Leadership, Social Media, and Technology in Integrated Islamic School Reputation Management - Nurdin Rivaldy; Encep Syarifudin; Hidayatullah (TA`DIBUNA, 2025)
Reputation management in Integrated Islamic Senior High Schools is crucial for enhancing competitiveness and public trust. This study analyses the influence of prophetic leadership, social media, and learning technology on reputation management, with teacher perceptions as a mediating variable. A quantitative method was employed through a survey of 109 respondents from six SMAITs in Bekasi. Data were collected using questionnaires and analysed with structural equation modelling (SEM). The findings indicate that prophetic leadership, the utilisation of social media, and learning technology have a positive and significant impact on school reputation management. Teacher perceptions strengthen the relationship between these three factors and school reputation. These results underscore the importance of developing prophetic leadership, optimising social media, and implementing learning technology effectively to enhance the reputation of SMAITs in Bekasi. Future research will broaden the focus to collaboration among parents, teachers, and students. Such collaboration, supported by digital innovation, is believed to strengthen further the image and public trust in integrated Islamic schools.